Dez Anos da PNEEPEI: uma análise pela perspectiva da biopolítica - Pagni, Pedro Angelo (2019)
Abstract: Amid the uncertainty of the current political context and an unprecedented institutional crisis in Brazil, this essay offers a theoretical analysis of the problems arising from the drafting, implementation and setback of PNEEPEI from a biopolitical perspective. To this end, supported by analyses by Foucault and Agamben, we will understand how Brazilian state governmentality addresses the inclusion of people with disabilities in school in terms of both biopolitics and Thanatos-politics. In light of the criticism of the scientific paradigm that brings together these two aspects underpinning PNEEPEI, we propose an aesthetic paradigm of inclusion to better meet the demands of the ethos of these people in school.